Carbonyl Activation by Selenium‐ and Tellurium‐Based Chalcogen Bonding in a Michael Addition Reaction. Issue 6 (21st January 2020) - Wonner, Patrick; Steinke, Tim; Vogel, Lukas; Huber, Stefan M.
Abstract: In the last years the use of chalcogen bonding—the noncovalent interaction involving electrophilic chalcogen centers—in noncovalent organocatalysis has received increased interest, particularly regarding the use of intermolecular Lewis acids. Herein, we present the first use of tellurium‐based catalysts for the activation of a carbonyl compound (and only the second such activation by chalcogen bonding in general). As benchmark reaction, the Michael‐type addition between trans ‐crotonophenone and 1‐methylindole (and its derivatives) was investigated in the presence of various catalyst candidates. Whereas non‐chalcogen‐bonding reference compounds were inactive, strong rate accelerations of up to 1000 could be achieved by bidentate triazolium‐based chalcogen bond donors, with product yields of >90 % within 2 h of reaction time. Organotellurium derivatives were markedly more active than their selenium and sulphur analogues and non‐coordinating counterions like BAr F 4 provide the strongest dicationic catalysts. Abstract : Make it active ! Tellurium‐based dicationic chalcogen bonding organocatalysts have been used to activate a carbonyl compound in the Michael addition reaction between indole derivatives and trans ‐crotonophenone. Up to 1000‐fold rate accelerations were observed compared to the corresponding iodinated halogen bond donor. Several comparison experiments were performed to rule out other modes of activation than chalcogen bonding.